Prioritizing Health Problems In Dukuh Demangan, Bantul, Yogyakarta Using Community Diagnosis And Hanlon Method - Ruliyandari, Rochana; Indah Purwanti, Dwi; Nur Djanah, Sitti; Solikhah, Solikhah; Nuraisyah, Fatma (CV. Inara, 2023)
Community diagnosis is an activity to determine the existence of a problem by collecting data on the community. Community diagnosis is an activity to explore the main issues faced by the community based on existing facts and take strategies and follow-up plans to resolve these problems. The study aimed to determine the description of health problems through community diagnosis in Dukuh Demangan, Sewon District, Bantul Regency. The method used in this research is quantitative andqualitative. The study design used in implementing the Field Learning Experience is adescriptive study. After determining the priority of the problem using the Hanlon method. The result shows that hypertension is the priority of health problems in Dukuh Demangan.